Participation of Rabs during Neuronal Development and Disease - Rozés Salvador, María Victoria (2019)
Membrane traffic has been widely studied in recent decades, and now it is clear that its participation in biologicalprocesses such as cellular migration, mitosis, and immune response, among others, is crucial and determinant.During the development of the nervous system, membrane trafficking organizes both the differential distributionand degradation of specific components, among others. Failures in these functions lead to the development ofneurological pathologies that can be progressive, chronic or even lethal such as Alzheimer´s, Huntington´s andParkinson´s diseases. These pathologies have significant health and economic costs in many countries. For thisreason, research is being focused on the study of those components (mainly proteins) involved in membrane trafficduring health and disease. In this short communication, we summarize main findings and state of the art discussionabout the functions of some membrane trafficking components during development, as well as the implications oftheir dysfunction into the progression of neurological pathologies.